Balinese Traditional House Architecture in Era 4.0 in Bukian - I Wayan Suky Luxiana; I Wayan Parwata; Agus Kurniawan (Architectural Research Journal, 2021)
Architecture is the art of designing buildings which are a microcosm of the universe. Traditional Balinese architecture is an embodiment of local wisdom in Bali which is inherited from generation to generation. In traditional Balinese architecture there is harmony between humans and creators, humans with humans and humans with nature. The background of this research is to identify the traditional Balinese architecture residence at 4.0 in Bukian. The purpose of this research is to find a formula or benchmark in building a traditional house using International Atropomometry. This makes it easier to build traditional houses due to the lack of Undagi in Bali. The method used is a quantitative method by making a sample house master plan to identify it with a flow chart. The results or conclusions of the natah pattern use the Tri Hita Karana concept, the barrier or floor uses the 1,0.8,0.6,0,4,0.2 approach. The approach in building a traditional house is SL= O+R+J+U.